Voor iedere vriend van de wetenschap. Het publiek van het naturaliënkabinet van de Hollandsche Maatschappij der Wetenschappen in de jaren 1772–1830 - de Beer, Liang (Studium, 2014)
This article explores the visitors of the natural history cabinet of the Holland Society of Sciences over the period 1772–1830. Not much is known about this first public museum in the Netherlands. By studying new sources such as visitor books and re-examining foreign travel accounts, the world of these visitors can be reconstructed. In this paper the role of the elite is put alongside Bennett’s thesis about the increasing public role of museums in Western society in the nineteenth century.